National Institutes of Health Stroke Scale Score Less Than 10 at 24 hours After Stroke Onset Is a Strong Predictor of a Favorable Outcome After Mechanical Thrombectomy. Issue 6 (19th December 2022) - Katano, Takehiro; Suzuki, Kentaro; Takeuchi, Masataka; Morimoto, Masafumi; Kanazawa, Ryuzaburo; Takayama, Yohei; Aoki, Junya; Nishiyama, Yasuhiro; Otsuka, Toshiaki; Matsumaru, Yuji; Kimura, Kazumi
Abstract : BACKGROUND: There are a few accurate predictors of patient outcomes after mechanical thrombectomy (MT). OBJECTIVE: To investigate whether the National Institutes of Health Stroke Scale (NIHSS) score 24 hours after stroke onset could predict favorable outcomes at 90 days in patients with acute stroke treated with MT. METHODS: Patients from the SKIP study were enrolled in this study. Using receiver operating characteristic curves, the optimal cut-off NIHSS score 24 hours after stroke onset was calculated to distinguish between favorable (modified Rankin Scale score 0-2) and unfavorable (modified Rankin Scale score 3-6) outcomes at 90 days. These receiver operating characteristic curves were compared with those of previously reported predictors of favorable outcomes, such as the ΔNIHSS score (baseline NIHSS score—NIHSS score at 24 h), percent delta (ΔNIHSS score × 100/baseline NIHSS score), and early neurological improvement indices. RESULTS: A total of 177 patients (median age, 72 years; female, 65 [37%]) were enrolled, and 109 (61.9%) had favorable outcomes. The respective sensitivity, specificity, and area under the curve values for an NIHSS of 10 were 92.6%, 80.7%, and .906; a ΔNIHSS score of 7 were 70.6%, 76.1%, and .797; and percent delta of 48.3% were 85.3%, 80.7%, and .890. CONCLUSION: NIHSS score <10 at 24 hours after stroke onset is a strong predictor of favorable outcomes at 90 days in patients treated with MT.